Pengaruh Konten YouTube Kids pada Channel Ryan’s World terhadap Sikap Anak Usia Dini - Rina Fitriyana; M. Sopyan (UNISBA Press, 2023)
Abstract. This study aims to identify the effect of YouTube Kids content on the Ryan's World channel on early childhood attitudes. The research was conducted by distributing 100 questionnaires to parents in the southern Sukabumi area who use YouTube Kids as a spectacle for their children through an online survey. This study uses social cognitive theory, which is a theory that focuses on quality, learning, and direct experience and explains why and knowing how the influence of the content can encourage them to imitate and follow what they see in the media. However, there are a number of factors in the learning process, namely the subject in the introduction of media characters to remember and understand what they see. by using quantitative data analysis methods and analyzed descriptively and measured using a likert scale. The sampling technique used is non-probability sampling. The population used in this study means South Sukabumi, which amounts to 303,907 people with samples taken by researchers, namely early childhood children aged 3-5 years who watch YouTube Kids Ryan's World shows. The reliability test used the Cronbach Alpha formula and the data processing technique used SPSS. The results showed that YouTube Kids content on Ryan's World Channel had a significant relationship with early childhood attitudes, which in the guideline for interpretation of the correlation coefficient the effect was included in the